Functional Outcome in Patients with Chronic Plantar Fasciitis Treated with Plantar Fascia Stetching vs Tendoachilles Stretching Exercises - Jha, RK; Uprety, S; Shah, LL (Journal of Institute of Medicine Nepal, 2013)
DOI: http://dx.doi.org/10.2126/joim.v35i1.8895 Journal of Institute of Medicine, April, 2013; 35:32-38